Association between hemoglobin and elevation among school-aged children: A verification of proposed adjustments - Kanu, Florence; Sharma, Andrea; Addo, O. Yaw; Suchdev, Parminder (American Society for Nutrition, 2020)
Anemia is defined by hemoglobin (Hb) lower than normal based on cutoffs specific to age and sex. Hb increases with elevation as a response to lower blood oxygen, thus adjusting Hb for elevation is necessary before applying cutoffs. Recent evidence among preschool-aged children (PSC) and reproductive-aged women (WRA) suggests current World Health Organization (WHO) recommended Hb elevation adjustments need updating. We examined the Hb and elevation association among school-age children (SAC) to confirm these findings.